Features of electronic and lattice mechanisms of transboundary heat transfer in multilayer nanolaminate TiA1N/Ag coatings - Kovalev, Anatoly I.; Wainstein, D. L.; Vakhrushev, V. O.; Gago, R.; Soldera, F.; Endrino, José L.; Fox-Rabinovich, German S.; Veldhuis, Stephen C. (Nature Publishing Group, 2017)
Plasmon resonance heterogeneities were identified and studied along Ag and TiAlN layers within a multilayer stack in nanolaminate TiAlN/Ag coatings. For this purpose, a high-resolution plasmon microscopy was used. The plasmons intensity, energy, and depth of interface plasmon-polariton penetration were studied by scanning reflected electron energy loss spectroscopy. The heat conductivity of such metal-insulator-metal (MIM) nanolaminate coatings was measured by laser reflectometry. Dependencies of thermal conductivity coefficient of coatings, MIM interfaces, and resistivity of Ag layers as a function of the Ag-TiAlN bilayer thickness were calculated on the basis of experimental data. The contribution of plasmon resonance confinement to the abnormal lower thermal conductivity in the MIM metamaterial with Ag layer thickness below 25 nm is discussed. In particular, the results highlight the relevant role of different heat transfer mechanisms between MI and IM interfaces: asymmetry of plasmon-polariton interactions on upper and lower boundaries of Ag layer and asymmetry of LA and TA phonons propagation through interfaces.